A case of fatal hyperammonaemic encephalopathy in a patient with end-stage Multiple Myeloma treated with daratumumab - Mauro Passucci; Francesca Fazio; Maria Teresa Petrucci (Mediterranean Journal of Hematology and Infectious Diseases)
n.